51 Determining the Best Indicators for Targeted Selective Treatment Against Gastrointestinal Nematodes in Sheep and Goats in Mississippi. (21st September 2022) - Dearborn, Lindsey; de Alvarez, Leyla Rios; Torres-Acosta, Juan Felipe
Abstract: Successful Targeted Selective Treatment (TST) against gastrointestinal nematodes (GIN) in small ruminant farms require the accurate measurement of phenotypic indicators of the animals. Specific indicators to predict the GIN burden include the age of the animal (A, years), bodyweight (BW, lbs), FAMACHAÓ (score from 1 to 4), body condition score (BCS, score from 1 to 5), and fecal egg count (FEC, eggs per gram of feces or EPG). Objective: Determine the indicator(s) that will more accurately contribute to TST for sheep and goats in the state of Mississippi (MS). Five (05) sheep and five (05) goat herds were used for data collection during fall 2021, the indicators of ewes (n=182) and does (n=197) were individually measured and FEC was determined using a modified McMaster technique. Statistical analysis was performed using Statistix for Windows v. 8.0., and two by two contingency tables were used to evaluate the association between FAMACHA and EPG, and BCS and EPG. The average indicators for sheep and goats sampled were, respectively, for A 2.91 and 2.98 years (P>0.05); BW 137.99 and 89.69 lbs. (P=0.0000); FAMACHA 2.53 and 2.99 (P=0.0000); BCS 3.25 and 2.98 (P=0.0000); FEC 510.05 and 487.56 EPG (P=0.0001). The correlations of FEC and FAMACHA for both species were positive 0.1753 (P=0.0006). Negative correlations were found for FEC and BCS of -0.1517 (P=0.0031) and for FAMACHA and BCS of -0.2945 (P=0.0000). The 2x2 contingency tables showed that goats with FAMACHA 4-5 had 37% chances to have >500 EPG compared to goats with FAMACHA 1-3 (28.2%) (P >0.05). Meanwhile, the BCS 1-2 resulted in 1.01-2.73 times more goats with >500 EPG (45.8% vs. 27.7%; P< 0.05). That effect was more evident for sheep, where 62.6% of animals with BCS 1-2 had >500 EPG vs. 15.8% with BCS 3-5, but the sample size was insufficient to assign statistical significance.